Multiscale finite element analysis of mode I delamination growth in a fabric composite. (1st December 2015) - Yamanaka, Tadayoshi; Ghiasi, Hossein; Heidari-Rarani, Mohammad; Lessard, Larry; Feret, Victor; Hubert, Pascal
Abstract: Mode I delamination of a five harness satin weave carbon fibre composite and the corresponding toughening mechanisms are studied using a multiscale finite element model of delamination growth in a double cantilever beam (DCB) specimen. The toughening mechanisms related to the fabric structure are studied by embedding a meso-scale model of the fibre architecture in the delamination zone into a macro-scale model of a DCB specimen. The R-curves and the load–displacement curves obtained from this analysis agree with the lower bound of the experimental results. The analysis identified two major toughening mechanisms: the inter-yarn locking ahead of the delamination front causing stress relaxation and the formation of sub-surfaces. Contribution of each toughening mechanism towards total delamination toughness is quantitatively evaluated, identifying the inter-yarn locking as the main source of toughening in mode I delamination of fabric composites. Video abstract: Multimedia 1 shows the different stages of the mode I delamination growth in a 5HS composite DCB specimen and its corresponding load–displacement curve.